2021
DOI: 10.21203/rs.3.rs-296959/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms Reveal Genetic Diversity in New Mexican Chile Peppers (Capsicum Spp.) 

Abstract: Background: Chile peppers (Capsicum spp.) are among the most important horticultural crops in the world due to their number of uses. They are considered a major cultural and economic crop in the state of New Mexico in the United States. Evaluating genetic diversity in current New Mexican germplasm would facilitate genetic improvement for different traits. This study assessed genetic diversity, population structure, and linkage disequilibrium (LD) among 165 chile pepper genotypes using single nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…In this regard, information from the flanking sequences for MQTL5.1 and MQTL5.2 identified in chromosome P5 will be utilized for the development of Kompetitive allele-specific (KASP ® ) [79] SNP assays for marker-assisted breeding. These KASP assays will be further validated using a recombinant inbred line population previously developed at New Mexico State University [80] and on a diverse population of New Mexican chile peppers [81] to screen for resistance to different races of P. capsici.…”
Section: From Meta-qtl To Marker-assisted Selection For Disease Resis...mentioning
confidence: 99%
“…In this regard, information from the flanking sequences for MQTL5.1 and MQTL5.2 identified in chromosome P5 will be utilized for the development of Kompetitive allele-specific (KASP ® ) [79] SNP assays for marker-assisted breeding. These KASP assays will be further validated using a recombinant inbred line population previously developed at New Mexico State University [80] and on a diverse population of New Mexican chile peppers [81] to screen for resistance to different races of P. capsici.…”
Section: From Meta-qtl To Marker-assisted Selection For Disease Resis...mentioning
confidence: 99%
“…Similarly, Soares et al (2020) reported significant environment × entry interactive effects for yield and fruit length, but not fruit width, after evaluating advanced habanero breeding lines in Brazil. Traits such as fruit size have been reported to be highly heritable in chile pepper (Stommel and Griesbach, 2008), including members of C. chinense (Lozada et al, 2021). A strong genotype contribution to the variability of fruit weight, as compared with the environment, has also been reported for chile pepper (Barchenger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%